Pintar Bookstore / Muhd Asyraf Ismail - Ismail, Muhd Asyraf (2021)
Pintar Bookstore is a business that it main item is books. It provided books that is suitable for all age. Pintar Bookstore were started it business since April 2021 with their objective to make the Malaysian people be a full of knowledge. Even with their hobby such as playing games, taking pictures or collecting stamps, we still want them to be knowledgeable citizens and care about current issues. Our item is long lasting item, so we just have a daily cleaning of our items. For every purchasing above RM50, we give free gift which is bookmark. We must make our shop looks special so that it would attract the customer.